Aira Kemiläinen: Finns in the Shadow of the »Aryans?«. Race Theories and Racism. Suomen Historiallinen Seura: Studia Historica 59. (Helsingfors, 1998). 320 s. - Kayser Nielsen, Niels (Historie/Jyske Samlinger, 2000)
-